2021
DOI: 10.21037/atm-21-2769
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of switching from crizotinib to alectinib in patients with advanced non-small cell lung cancer with anaplastic lymphoma kinase fusion

Abstract: Background: Alectinib and crizotinib have been approved as first-line therapies for advanced non-small cell lung cancer (NSCLC) with anaplastic lymphoma kinase (ALK) gene fusion. However, the therapeutic efficacy and side effects are still largely unknown of patients who switched to next-generation ALK tyrosine kinase inhibitors (ALK-TKIs), such as alectinib, after experiencing no disease progression with initial crizotinib treatment.Methods: This prospective real-world study enrolled patients who were treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…A prospective study confirmed that such patients still experience significant therapeutic benefits (10).…”
Section: What Is the Implication And What Should Change Now?mentioning
confidence: 82%
See 1 more Smart Citation
“…A prospective study confirmed that such patients still experience significant therapeutic benefits (10).…”
Section: What Is the Implication And What Should Change Now?mentioning
confidence: 82%
“…Some ALK -positive NSCLC patients are unable to tolerate the adverse reactions of crizotinib, thus, requiring a switch to alectinib. A prospective study confirmed that such patients still experience significant therapeutic benefits ( 10 ).…”
Section: Introductionmentioning
confidence: 83%
“…Furthermore, it has exhibited remarkable effectiveness against several novel ALK fusion proteins, including VKORC1L1–ALK [ 91 ], SQSTM1–ALK [ 92 ], HIP1–ALK [ 93 ] and STRN–ALK [ 94 ]. For patients whose disease progression persists despite initial treatment with Crizotinib, converting to Alectinib may be a viable option that could enhance treatment compliance [ 95 ]. Patients undergoing Alectinib treatment commonly exhibit elevated levels of creatinine phosphokinase and may experience neutropenia [ 79 ].…”
Section: The Development Of Inhibitors Targeted Kinase Fusion Proteinsmentioning
confidence: 99%
“…In a final analysis of the J-ALEX study, compared to crizotinib, alectinib did not achieve overall survival (OS) benefit ( 60 ), reflecting that the crossover to the post first-line treatment might greatly influence OS, especially in ALK+ NSCLC who could get significant benefit from all ALK TKIs. A prospective real-world study investigated the strategy of switching to alectinib in ALK+ NSCLC patients that did not experience disease progression with initial crizotinib ( 61 ). The results indicated that an early switch from crizotinib to alectinib might be a viable option and may promote better treatment compliance.…”
Section: Alk Targeted Therapies In Nsclcmentioning
confidence: 99%